Exploring the Implementation of Digitalization and Business Innovation on SME Performance of at Gudang Ayam Potong Bu Haji Mala - Rosalinda Rosalinda; I Gusti Ngurah Widya Hadi Saputra; Putu Dyah Permatha Korry; Nilna Muna (Journal of Innovative and Creativity, 2026)
This study explores the implementation of digitalization and business innovation to improve the performance of MSMEs at Gudang Ayam Potong Bu Haji Mala, Denpasar, Bali. The background of this research is the need for digital transformation in the Industry 4.0 era in the dynamic food sector, where MSMEs, as the backbone of Indonesia’s economy, must adapt to face globalization. This research uses an exploratory qualitative method with triangulation techniques, namely in-depth or semi-structured interviews, observation, and documentation of the owner, manager, administrative staff, and social media staff at Gudang Ayam Potong Bu Haji Mala. The choice of qualitative method aims to understand in depth the processes, strategies, and challenges encountered in adopting digitalization and business innovation. The results show initial digitalization through social media, QRIS/bank transfer transactions, and digital record-keeping, but are constrained by human resources and infrastructure. Business innovation includes product diversification (fillet, marinades, hampers), production efficiency through modern tools, and digital marketing strategies that increase sales, efficiency, and customer satisfaction. This research contributes theoretically to MSME innovation management and practically as a reference for digital strategies for business actors and the government.